The Content Analysis of Rorschach in Attesting the Sex Offenders - Lathifah Hanum; Alfath Hanifah Megawati; Cantyo Atindriyo Dannisworo; Bona Sardo Hasoloan Hutahaean; E. Kristi Poerwandari (Jurnal Psikologi, 2021)
The Rorschach test is one of the psychological tests widely used in various assessment settings, including in studies related to sexual offenses. However, such research is scarce, although the level of sexual violence in Indonesia increases yearly. Sexual violence is often associated with the sexual drives that humans have in themselves. In this case, Rorschach can provide an overview of the individual's drives, ideas, and social relationships. The current study aims to find the personality profiles of sex offenders. Therefore, this study collected Rorschach data from 46 male sex offenders over 11 years in Depok City, Indonesia. Based on content analysis, this study found several prominent characteristics of sex offenders, such as exhibited difficulties in adaptation due to low intellectual capacity, poor emotional regulation, and empathy that other causes difficulty to build strong relationships with others. They also suppress sexual urges, but they were more likely to express it impulsively with low intellectual capacity and emotional regulation. These various personality characteristics possessed by sex offenders will undoubtedly impact the intervention process they go through to gain insight from their experience. The results are expected to be an input for developing interventions for sex offenders not to repeat their actions in the future.